A Model-Based Approach to the Control of Incremental Ash in Coal Flotation (Society for Mining, Metallurgy & Exploration, 1999)
The objective of the fines flotation step in a coal preparation plant is to maximize coal recovery subject to a constraint on the allowable ash in the concentrate. The objective is achieved when the incremental ash is driven to a target value determined by an economic constraint. In this paper, a phenomenological flotation model and ash analyzer combination are identified that allow the development of a soft sensor for incremental ash and subsequently a model-based strategy which manipulates key flotation variables to achieve the control objective. A combination of plant tests and computer simulations are presented to evaluate control-system performance in one operation.